Von Willebrand factor and gastric cancer – is there an association? – A pilot study from South India - S, Karthikeyan; Niyas Ahamed; Sastha A; Villalan R; Rajnihedan KG; Padmanabhan S; Govindan, Ramajayam; Mahesh Kumar (Asian Journal of Medical Sciences, 2024)
Background: Gastric adenocarcinoma in Indian patients’ is on the rise. A high level of plasma von Willebrand factor (vWF) is associated not only with the development of cancerassociated thrombosis but also with the degree of malignancy, the rate of metastasis, and cancer prognosis. Aims and Objectives: The aim of this study was to study the association of vWF with tumor location, TNM staging, and grades of tumor differentiation in gastric adenocarcinoma and to assess the usefulness of circulating vWF levels as a potential biomarker for gastric adenocarcinoma. Materials and Methods: This study is a prospective observational study done in the Department of Surgical Gastroenterology, Madurai Medical College, Madurai, over a period of 2 years between September 2020 and August 2022. Fifty cases of gastric cancer and 50 controls were recruited and vWF levels were analyzed. Results: Among the 50 gastric cancer patients, 8% belonged to Stage II, 62% belonged to Stage III, and 30% belonged to Stage IV. vWF was elevated in Gastric Cancer patients compared to control group. Mean value of vWF in Cases and Control population was 3.68 ng/ml and 0.58 ng/ml respectively (p value 0.0005). Pertaining to Stage, the vWF value was, Stage II – 4.7, Stage III – 3.3, and Stage IV – 4.1 ng/mL. With respect to tumor differentiation, the vWF values were, poorly differentiated – 4.7, moderately differentiated – 3.0, and well differentiated – 3.9 ng/mL. Conclusion: vWF values were significantly elevated in gastric cancer patients. Based on the results, vWF can be used as a surrogate marker to predict the tumor differentiation in patients, thereby prognosticating the disease. Stage-wise, there was no significant difference in the vWF values.